2001
DOI: 10.1177/03635465010290011301
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Injuries in Pole-Vaulters

Abstract: Pole vaulting is a unique sport in that athletes often land from heights ranging from 10 to 20 feet. We retrospectively reviewed 32 catastrophic pole-vault injuries that were reported to the National Center for Catastrophic Sports Injury Research between 1982 and 1998. The purpose of this study was to determine the mechanisms of injury so that preventive strategies can be implemented. Information was obtained by means of a telephone interview with someone familiar with the accident. All injuries occurred in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…For example, the registry has tabulated 22 trauma-associated deaths with pole vaulting in this young age group, predominantly from head injuries when athletes fall outside the padded landing pit. 12 Although the precise number of at-risk competitors in this sport is unknown, the mortality risk associated with pole vaulting would nevertheless seem to be particularly high. Similarly, competitive cheerleading was associated with 3 trauma-related deaths.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the registry has tabulated 22 trauma-associated deaths with pole vaulting in this young age group, predominantly from head injuries when athletes fall outside the padded landing pit. 12 Although the precise number of at-risk competitors in this sport is unknown, the mortality risk associated with pole vaulting would nevertheless seem to be particularly high. Similarly, competitive cheerleading was associated with 3 trauma-related deaths.…”
Section: Figurementioning
confidence: 99%
“…6 Most previous reports of blunt trauma that cause structural organ damage have been tabulated during relatively short time periods, often including early eras of risk or largely confined to nonfatal events in small cohorts, and in single sports. 5,[7][8][9][10][11][12] In addition, the risks associated with previous head blows and concussions have been the subject of substantial recent attention in the media and medical literature. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For these reasons, we believe it is timely to interrogate our large US national registry, assembled throughout 30 years, to assess the epidemiology and frequency of traumarelated sudden deaths in children, adolescents, and young adults aged 21 years and younger engaged in competitive athletics, compared with the incidence of those events caused by cardiovascular disease over the same period.…”
mentioning
confidence: 99%
“…In 135 collegiate pole vaulters aged 20.6 ± 1.4 years, Rebella ( 2015 ) reported a quite similar injury incidence of 7.9 injuries per 1,000 athlete-exposures, with 15% of injuries leading to season-ending, although the majority of injuries lead to an average time-loss of 9 days (Rebella, 2015 ). But it is important to note that catastrophic injuries have also been described (Boden et al, 2001 , 2012 ). In other epidemiological studies on injuries in athletics, pole vaulters were included in the groups of jumpers making impossible the distinction of the specific injury risk and characteristics of pole vaulters (Watson and Dimartino, 1987 ; D'Souza, 1994 ; Bennell and Crossley, 1996 ; Edouard et al, 2011 , 2015a , b ; Jacobsson et al, 2012 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of such injuries is increased because pole vaulters may fall from a great height. Boden et al 2,3 investigated catastrophic injuries in pole vaulters and reported landing risks. Those investigators found that increasing the size of the mat resulted in fewer catastrophic injuries.…”
Section: Discussionmentioning
confidence: 99%